Managing electric vehicle power - Davis, Samuel (SAE International, 2020)
This book provides complete coverage for understanding how best to utilize the primary power source across all the EV's Electric Control Units. Readers will also be introduced to the qualification standards of the Automotive Electronics Council (AEC). AEC standards are a 'one-time' qualification that typically takes place at the end of the development cycle.
Keywords: Electric automobiles.; Automobiles -- Batteries.; Electric batteries.; elektronické knihy; electronic books